South Africa Economic Update, July 2012 : Focus on Inequality of Opportunity - World Bank (World Bank, Washington, DC, 2017)
Section one provides an economic update and assesses the challenges and near-term prospects facing the South African economy. In particular, it looks at the implications for South Africa of the resurgence of uncertainty in global financial markets, the surge in capital flows to safe-haven assets, the continuing Euro zone crisis, and signs of slowdown in some of the large emerging market economies. Section two focuses on inequality of opportunity in South Africa. For the first time, using innovative techniques, this section presents an analysis of the interlinked inequality of opportunities for children and for access to employment. Every society has a degree of inequality of outcomes that reflects differences in innate human capabilities, effort, education, experience, and skills. But a recognized goal for public policy is to ensure at least the equality of opportunity for every individual in a country. Many countries have used this new approach to develop targeted policies to promote such equality of opportunity and to monitor and evaluate the success of public programs.